The effect of Rutin hydrate on Glucocorticoids induced osteoporosis in mandibular alveolar bone in Albino rats (Radiological, histological and histochemical study) - Nuha Abdul-Fattah Baraka; Naglaa Fathallah Ahmed; Safaa Ismail Hussein (Elsevier, 2022)
Background: Glucocorticoids are used in different conditions such as autoimmune disorders and organ transplantation and their administration is the most common cause of secondary osteoporosis. Rutin is a flavonoid found in many plants. Flavonoids are natural products with various therapeutic and biological effects. Objective: Is to investigate the effect of Rutin Hydrate as a form of Rutin on glucocorticoid induced osteoporosis in mandibular alveolar bone radiologically, histologically and histochemically. Methods: Twenty-one adult male Albino rats were randomly divided into three groups. Group I (control), group II (osteoporotic) and group III (Rutin Hydrate treated). In both group II and III rats received 21 mg/kg of methylprednisolone daily for four weeks. Then group III received 50 mg/kg of rutin hydrate in distilled water daily for another four weeks. At the end of the experiment, mandibles were dissected for radiographic assessment, then processed for histological and histochemical examination and statistical analysis. Results: Radiologically, administration of Rutin Hydrate was able to enhance bone density than osteoporotic group. Histological examination revealed preserved cortical bone thickness that had been statistically proved. Apparently normal sized marrow cavities, some plump osteoblasts and normal osteocytes were seen in group III. Histochemical examination showed statistical increase in the area percentage of newly formed collagen in group III than group II. Conclusions: Rutin Hydrate was able to modify the radiological and histological picture of osteoporotic alveolar bone. This was achieved by the ability of Rutin Hydrate to increase bone density, preserve cortical plates thickness and enhance new collagen formation that was proved histochemically.